A computer simulation study of the influence of microwave sensitisation on interaction between nanoparticles and cell membrane. Issue 6 (13th April 2021) - Yue, Kai; Jin, Xiucheng; Wei, Yiang; Zhong, Weishen; Zhang, Genpei; Zhang, Xinxin
ABSTRACT: Microwave heating combined with the use of susceptible materials shows potential to enhance nanoparticle (NP)-mediated drug delivery. Understanding the mechanism of their synergistic action on NP transmembrane is helpful for NP design and biocompatibility assessment. The influence of microwave sensitisation on cell membrane fluidity and permeability was investigated through molecular dynamic simulation. On the basis of NP–cell membrane interactions, the transmembrane transport was simulated for the concerned NPs potentially used in biomedical applications. Results show that microwave sensitisation can increase the cell membrane fluidity and permeability and decrease the phospholipid orderliness compared with microwave irradiation. The effect of sensitising materials on membrane structure is very slight under no microwave irradiation. The penetration of positively charged hydrophobic and hydrophilic NPs into the cell membrane can be promoted by applying either microwave irradiation or microwave sensitisation, with the latter having more remarkable effect than the former. The positively charged hydrophobic NPs can penetrate into the membrane more easily than the hydrophilic NPs although their temperature increases are lower. Moreover, the microwave sensitisation enables uncharged hydrophobic NPs to translocate across the membrane whereas the NPs remain stabilised on the surface layer of the membrane when no or only microwave irradiation is applied.